XRF core scanning of composite sediment core BIS-2000 - Stefan Lauterbach; Frank Harald Neumann; Rik Tjallingii; Achim Brauer (PANGAEA, 2024)
The data set bundle comprises geochemical, XRF core scanning and pollen data from composite sediment core BIS-2000, which was compiled from two parallel sediment cores (BIS-1 and BIS-3) obtained near Bispingen, northern Germany (53.071528°N, 9.989861°E, 82.0 m). BIS-2000 comprises Last Interglacial (Eemian) to early Last Glacial (Weichselian) palaeolake deposits, which cover the section between 15.55 and 30.68 m composite depth. The data set Bispingen BIS-2000 XRF contains results of XRF core scanning. Analyses were carried out at the GFZ German Research Centre for Geosciences in Potsdam, Germany, on the section between 15.08 and 31.20 m composite depth. Split sediment core segments were scanned with an ITRAX XRF core scanner and measured intensities of silicon, calcium and titanium were used to calculate the log-ratios log(Si/Ti) and log(Ca/Ti).